Associational effects and indirect interactions - the dynamical effects of consumer and resource traits on generalist-resource interactions - Klapwijk, M; Bonsall, M (Ecological Society of America, 2022)
Trophic interaction modifications occur in food webs when the direct or indirect interaction between two species is affected by a third species. These behavioral modification effects are often referred to as associational effects. Changes in focal resource availability and consumption by a generalist herbivore can affect a range of outcomes from resource exclusion to multiple resources coexisting with the focal plant species. Here, we investigate the indirect interaction between a focal and alternative resource mediated by a generalist consumer. Using theoretical approaches we analyse the conceptual link between associational effects (both resistance and susceptibility) and the theory of apparent competition and resource switching. We find that changes in focal resource traits have the potential to affect the long-term outcome of indirect interactions. Inclusion of density-dependence expands generalist life-histories and broadens the range where, through associational effects, the availability of alternative resources positively influence a focal resource. We conclude that different forms of associational effects could, in the long-term, lead to a range of indirect interaction dynamics, including apparent competition and apparent mutualism. Our work aims to connects the theoretical body of work on indirect interactions to the concepts of associational effects. The indirect interactions between multiple resources need more thorough investigation to appreciate the range of associational effects that could result from the dynamical interaction between a generalist consumers and its focal and alternative resources.